Pola Asuh Pembina Asrama (Boarding School) Dalam Meningkatkan Karakter Religius Siswa SMP Insan Cendekia Madani Serpong Tangerang Selatan Banten - Nurtianty, Tetra; Siskandar, Siskandar; Bahri Tanrere, Syamsul (Journal of Education and Islamic Studies (JEIS), 2025)
The formation of religious character is an essential aspect of character education, emphasizing thoughts, words, and actions grounded in religious values. In dormitory-based schools, the dormitory supervisors play a crucial role as substitute parents, teachers, and role models for students. This study explores the parenting patterns used by dormitory supervisors at SMP Insan Cendekia Madani in shaping students' religious character. Using a qualitative approach, data were collected through observation, interviews, and documentation. The findings reveal that religious character development requires structured strategies, including exemplary methods, habituation, direct practice, prayer, and affection. The study also identifies challenges from students' internal conditions, parental upbringing inconsistencies, and environmental factors. An adaptive and situational parenting style, tailored to students' characteristics, proves effective. The research concludes that dormitory parenting patterns significantly contribute to enhancing students' religious character and offers insights for better management in Islamic boarding schools.